Resistensi Pribumi Terhadap Kolonial Belanda Dalam Novel Salah Asuhan - Waskyto Sugiyanto, Bagus Ajy (Jurnal Ilmu Komunikasi AKRAB, 2019)
ABSTRACTThe standardization of the rules imposed strictly by Balai Pustaka in the Dutchcolonial era made it difficult for novel authors to convey messages that smelled ofResistance to the Dutch government. Novel Salah Asuhan written by Abdoel Moeis is oneof the novels published by the Balai Pustaka era, although it is often said that BalaiPustaka writers reinforce romance, but this research aims to see the forms of indigenousresistance to the colonial parties contained in the Salah Asuhan novel. The study usesconcepts in postcolonial theory namely mimicry and resistance which are used asspectacles of analysis, while the method used is a qualitative research method. Theprocedure in this method is to collect descriptive data in the form of words or events thatcan be observed. The data source in this study is a document. The document in questionis the novel Salah Asuhan by Abdoel Moeis published by Balai Pustaka in 1995. Researchfindings show that there are two forms of resistance used against the Dutch colonial.First, soft resistance or mimicry towards Dutch-style culture and knowledge systems,such as education, use of language, furniture, clothing, work, and marrying Westerners.The second resistance is absolute / firm resistance, shown in the rejection of Dutchcolonial practices which appear in the analogy of the Bird of the Garudadikotomibetween urban space (Batavia) and village (Padang) which represents modern / Westernand traditional / indigenous views.Keywords: Salah Asuhan Novel, Balai Pustaka, Resistance, Mimicry